Association of unhealthy dietary behaviors with renal function decline in patients with diabetes. Issue 1 (7th January 2020) - Lin, Cheng-Wei; Chen, I-Wen; Lin, Ying-Tzu; Chen, Hsin-Yun; Hung, Shih-Yuan
Abstract : Objective: Balanced nutrition is important for patients with diabetes, and nutrition might well influence diabetes-related complications, although there is limited evidence for this supposition at present. Consequently, we investigate the association between dietary behaviors and renal function decline among patients with diabetes. Research design and methods: From 2011 to 2013, a total of 2797 patients with type 2 diabetes participated in the D iabetes Shared Care Program at Chang Gung Memorial Hospital. All received nutritional consulting by dieticians and an eight-item list of unhealthy dietary behaviors, which included the excessive intake of carbohydrates, fats, protein, fruit, pickled foods, dessert and alcohol, as well as inadequate dietary vegetable. Estimated glomerular filtration rate (eGFR) decline ≥40% was defined as a surrogate end point for kidney damage. Independent dietary risk factors predicting poor renal outcomes were assessed. Results: Stable mean glycated hemoglobin (A1c ) (7.78% to 7.75%, p=0.151), improved cholesterol (174.04 to 170.13 mg/dL, p<0.001) and low-density lipoprotein (104.19 to 98.07 mg/dL, p<0.001) were found in patients throughout 2 years of therapy. However, significant eGFR decline was noted (94.20 to 88.08 mL/min/1.73 m 2, p<0.001). A total of 125 subjects had eGFR decline ≥40% and 2672 had stable renal progression. In regression analysis, 625 stable renal patients (selected via propensity score matching) and 125 subjects with eGFR decline ≥40% demonstrated excessive pickled foods to be predictive of poor renal outcomes (OR 1.861, 95% CI 1.230 to 2.814, p=0.003). Conclusions: Our study suggests that excessive pickled foods deteriorate renal function more than other unhealthy dietary behaviors in patients with diabetes.